Analysis of the Role of the Flo Application as a Digital Educational Media for Adolescent Reproductive Health in the Technology Era - Ramadhanti, Auliya; Farhan , Hira; Allaham, Amenah; Ismail, Mazen A. (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This study aims to analyze the role of the Flo application as a digital educational media based on AI in improving adolescent knowledge, attitudes, and behavior related to reproductive health in the era of modern technology. Methodology: This study uses a qualitative approach with a descriptive analytical method to explore the experiences, perceptions, and impacts of using the Flo application on adolescents in the context of reproductive health education. Data were collected through in-depth interviews, questionnaires, observations, and documentation studies. The sampling technique used was purposive sampling, while data analysis was carried out with a thematic approach for qualitative data and descriptive statistics for quantitative data. Main Findings: The results showed that the Flo app was effective in increasing adolescents' understanding of reproductive health, with the majority of respondents feeling more confident in managing their menstrual cycles and maintaining their health. The most appreciated features were cycle prediction and daily symptom logs. Although the app had a positive impact, there were obstacles such as limited access to premium features and difficult-to-understand medical terms. Overall, the Flo app was well received by users and showed potential for further development. Novelty/Originality of this study: This study offers novelty by exploring the role of the Flo app that uses AI to predict menstrual cycles and provide personalized reproductive health education content. Unlike previous studies, this study leverages an app that is already widely available, opening up opportunities to develop a more relevant and effective digital education platform for adolescents.